Role of Institutions in Agriculture and Food Security: A Social Network Analysis of the Bonda Tribal Communities of Odisha, India (Indian Journal of Extension Education, 2025)
The study focuses on the Bonda tribe, a Particularly Vulnerable Tribal Group (PVTG) residing in the ecologically fragile Bonda Hills of Odisha, India. It explores the transformative role of institutions in agriculture and food security across three altitudinally distinct villages, Kadamguda, Badbel, and Andrahal, using a sequential exploratory mixed method approach. Tools like focus group discussions, participatory rural appraisal, household surveys, and social network analysis were employed to map institutional presence and community interaction. Findings reveal varying levels of social cohesion and institutional embeddedness. Kadamguda demonstrates strong intra-village ties and effective institutional linkages, while Badbel and Andrahal reflect weaker community networks despite broader institutional outreach. The Bonda Development Agency (BDA) emerges as a pivotal actor connecting tribal households with service providers such as Integrated Tribal Development Agency (ITDA), Watershed Support Services and Activities Network (WASSAN), Madhyam, and the Agriculture Department, Government (Govt.) of Odisha. The study highlights that institutional presence alone is insufficient; local leadership, social capital, and community trust critically shape outcomes. For institutions to be effective, interventions must prioritise cultural sensitivity, participatory governance, and inter-agency convergence. Strengthening institutional responsiveness alongside local social networks is essential for building resilient, community-driven food systems in tribal regions.